Design of a Web-Based School Profile at Northern Green School Medan Using the Importance Performance Analysis Method - Destisonya Buulolo; Jackri Hendrik; Octara Pribadi (SEAN Institute, 2025)
School profile website in today's education world is very important, to convey information and school identity to the public. Currently, SD Northern Green School Medan does not have one that can function as a means of promotion that presents various important information such as school name, location, vision and mission, student achievements, gallery, and contacts that can be reached by parents and the public who want to register their children at SD Northern Green School Medan. This study aims to design a web-based school profile that is able to meet the information needs of users. The method applied in this study is the Importance Performance Analysis (IPA) Method, which helps in identifying the required attributes and evaluating their performance from the user's perspective. Data were obtained through direct observation and distributing questionnaires to 50 respondents. The results of the analysis using the Importance Performance Analysis (IPA) method show that elements such as school profile, achievements, activity gallery, and contact information are important parts that must be on the SD Northern Green School Medan website. This website was developed using HTML, PHP, and MySQL. With the presence of this website, it is hoped that the school will be able to be more effective in conveying information and improving the reputation of SD Northern Green School Medan in the current digital era.